The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1159/000512726
|View full text |Cite
|
Sign up to set email alerts
|

IgG4 Expression in Patients with Eosinophilic Otitis Media

Abstract: Objective: Eosinophilic otitis media (EOM) is an intractable middle ear disease recognized by an eosinophil enriched middle ear effusion and mucosa. Although precise pathogenesis of EOM remains unclear, it is characterized by type 2 inflammation. Since IgG4 is an IgG subclass induced by type 2 cytokines such as IL-4 and IL-13, we sought to characterize and compare local IgG4 expression in patients with and without EOM. Methods: Twelve patients with bilateral profound hearing loss, 9 of which underwent a cochle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
(19 reference statements)
0
2
0
1
Order By: Relevance
“…En cuanto a la relación entre otitis media eosinofílica y ER-IgG4, en un estudio se sugiere que la ER-IgG4 puede contribuir al desarrollo de esta, aunque solo en 2 de los 48 pacientes de nuestra revisión se les diagnosticó una OME 47 . Con lo cual parece más una presentación excepcional dentro de la ER-IgG4.…”
Section: Discussionunclassified
“…En cuanto a la relación entre otitis media eosinofílica y ER-IgG4, en un estudio se sugiere que la ER-IgG4 puede contribuir al desarrollo de esta, aunque solo en 2 de los 48 pacientes de nuestra revisión se les diagnosticó una OME 47 . Con lo cual parece más una presentación excepcional dentro de la ER-IgG4.…”
Section: Discussionunclassified
“…Previous studies have not provided analyses of the OME effusion proteome database or disease differential analyses. [4][5][6] With advancements in proteomic techniques, a more inclusive analysis is needed to realize the function of middle ear effusion. Moreover, previous studies have indicated that the pathogenesis of OME is associated with immune response, coagulation activities, and inflammatory disorders.…”
Section: Introductionmentioning
confidence: 99%
“…OME was defined as an infection-free disease in the past. 4 However, recent studies have challenged this definition by demonstrating bacterial colonization in the middle ear charge or mucosa of patients with OME. These findings have raised questions regarding the existing theories of the disease’s etiology.…”
Section: Introductionmentioning
confidence: 99%